Analysis of the best method for completion of rainfall missing data in high areas of Camaná and Chili basins, Arequipa, Peru - Ramos Alonzo, Robert (2019)
In all of Peru, there are not enough weather stations that could provide climate data and in view of this need, in the present investigation the application of different methods is analyzed in order to complete missing data in four rainfall stations in the areas located between 4000 to 4500 msnm of the Arequipa region. These methods are; linear regression, distance ratios, neighborhood averages, correlation with neighboring stations, multiple regression, and completion has been added by the regional vector method. The methods are analyzed through the Determination Coefficient (R2), Standard Estimation Error (EEE), Bland and Altman concordance test, establishing the best estimator in this region.